2006
DOI: 10.1124/jpet.106.116004
|View full text |Cite
|
Sign up to set email alerts
|

Single Exposure to a Serotonin 1A Receptor Agonist, (+)8-Hydroxy-2-(di-n-propylamino)-tetralin, Produces a Prolonged Heterologous Desensitization of Serotonin 2A Receptors in Neuroendocrine Neurons in Vivo

Abstract: We previously demonstrated colocalization of serotonin 1A (5- . This is the first in vivo demonstration of a prolonged heterologous intracellular desensitization of 5-HT 2A receptors after acute activation of 5-HT 1A receptors. These findings may provide insight into the long-term heterologous interactions between 5-HT 1A and 5-HT 2A receptor signaling that could occur in response to antidepressants, antipsychotics, or drugs of abuse that target these receptor subtypes.HTSerotonin (5-HT), a known stimulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This result suggests that the improvement brought about by yokukansan in aggressive behaviour or head‐twitch response is not due to its direct antagonism of 5‐HT2A receptors. Recently, Carrasco et al 29 . and Wieland et al 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that the improvement brought about by yokukansan in aggressive behaviour or head‐twitch response is not due to its direct antagonism of 5‐HT2A receptors. Recently, Carrasco et al 29 . and Wieland et al 35 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that 5‐HT and 5‐HIAA concentrations are decreased in most regions of the brain by a single injection of PCA 20 . In this study, the 5‐HT concentration and high‐K + ‐elicited 5‐HT release were examined in the hypothalamus as a representative of the terminal areas of serotonergic innervation, because the hypothalamus is known to be important in regulating aggressive response and emotional behaviour 28,29 as well as an area of the brain rich in 5‐HT 30 . PCA decreased both the 5‐HT concentration and 5‐HT release in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…2A receptors display a lower affinity for 5-HT, and are more prone to agonist-induced desensitization, than are 1A receptors (for review, see Zifa and Fillion, 1992), suggesting that tonic release of low concentrations of 5-HT may preferentially inhibit overall cortical output. However, 1A and 2A receptors are susceptible to heterologous desensitization (Zhang et al, 2001; Carrasco et al, 2007), raising the possibility of complex interaction among 1A and 2A signaling in vivo . Additional studies will be necessary to explore the response of COM and CPn neurons to tonic exposure to physiological concentrations of 5-HT, and to endogenous release of 5-HT in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that these interactions may play an important role in the control of some physiological functions including behavioral reactions and hypothalamic neurosecretion [88][89][90]. Its disturbances have been reported to underlie a variety of mental disorders [91,92].…”
Section: Serotonin Receptors In Neuroimmunomodulationmentioning
confidence: 98%
“…It is established that the clinical efficacy of classical antidepressants, selective inhibitors of 5-HT reuptake, at least partly, is provided by their ability to restore a disturbed balance between the 5-HT-receptor subtype [93]. Some authors have shown the potentiating interactions between 5-HT 1A -and 5-HT 2A -receptors, while others indicated functional opposition or antagonistic interactions [87][88][89][90]93]. As was demonstrated recently, the genes encoding the two receptor subtypes are involved in the process of their interaction.…”
Section: Serotonin Receptors In Neuroimmunomodulationmentioning
confidence: 99%